Effects of reinforcing bars in ultrasonic pulse and rebound number measurement in concrete - Venus, Mary Jane F.; Antonio, Oscar Victor M. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
This study aims to investigate the effects of reinforcing bars in ultrasonic pulse and rebound number measurement in concrete. Reinforced concrete and mortar specimens with varying diameter, depth and spacing or reinforcing bars were tested using the rebound hammer and ultrasonic testing. The behavior of the waveform obtained from the ultrasonic test and the effect of aggregates were also studied. It was found out that the presence of rebar generally decreases the pulse velocity in mortar significantly. However, no significant relationship was found in the effect of rebar diameter and ultrasonic pulse velocity in mortar and concrete specimens. Attenuation in the presence of reinforcing bars also did not increase as expected. The rebound number was found to be increasing due to aggregates but did not show any significant relationship in the effect of reinforcing bars. Possible sources of error might have come from the irregularity of the surface of the specimen where rebound hammer and ultrasonic tests were conducted. The curing condition of the specimens may have also affected the development of interaction of the components of the concrete inside the specimen.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Reinforcing bars -- Testing